Pemahaman sederhana tentang hadis mutawatir,ahad,masyhur,aziz,dan gharib - zahra, fany fadhilatuz (Maliki Interdisciplinary Journal, 2026)
Understanding the Prophet's hadith is crucial because of its position as the primary reference after the Quran in Islamic teachings. Unlike the Quran, which was written down from the beginning, hadith were transmitted through memorization and narration by the Companions, who were known for their meticulousness and carefulness. Therefore, when studying hadith, one of the key considerations is how they are classified based on the number of narrators. This study focuses on two major groups of narrations: mutawatir hadith and ahad hadith. Within the ahad hadith group, there are several other types of derivatives, such as famous, aziz, and gharib hadith. Mutawatir hadith are narrations transmitted by numerous narrators throughout each generation, thus minimizing the possibility of error or fabrication. Conversely, ahad hadith are narrations that do not have as many narrators as mutawatir hadith, and are therefore further subdivided based on the number and quality of their narrators. Broadly speaking, the science of hadith typically discusses five main categories: mutawatir, ahad, masyhur, aziz, and gharib. Each of these five forms has its own characteristics that serve as the basis for assessing the strength, validity, and certainty of a narration.